1993
DOI: 10.1039/c39930000670
|View full text |Cite
|
Sign up to set email alerts
|

Novel dehydrative ring transformation of 1-alkyl-3-aroylpyrrolidines into 1-alkyl-2-aryl-3-methylpyrrole derivatives

Abstract: Poly-functionalized pyrroles 4, 5 and 6 were prepared in a good to high yield by a dehydrative ring transformation of 3-aroylpyrrolidine derivatives 1 , 2 and 3 in ethylene glycol a t 130 "C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Pyrrole 4p , with three different substituents on the pyrrole ring, could be easily constructed by this method (entry 16). It was noted that the methods for the regioselective synthesis of multisubstituted pyrroles with different substituents from the easily accessible starting materials under mild reaction conditions are limited . In addition, azadiene 1j bearing one more substituent (Me group) at the C-2 position could also smoothly react with benzoyl cyanide to give the fully substituted pyrrole 4q in 46% yield (entry 17).…”
Section: Resultsmentioning
confidence: 94%
“…Pyrrole 4p , with three different substituents on the pyrrole ring, could be easily constructed by this method (entry 16). It was noted that the methods for the regioselective synthesis of multisubstituted pyrroles with different substituents from the easily accessible starting materials under mild reaction conditions are limited . In addition, azadiene 1j bearing one more substituent (Me group) at the C-2 position could also smoothly react with benzoyl cyanide to give the fully substituted pyrrole 4q in 46% yield (entry 17).…”
Section: Resultsmentioning
confidence: 94%
“…Mataka et al [36] found that the pyrrolidines 59 Ϫ obtainable by easy procedures [37] Ϫ when heated in ethylene glycol for some hours afford 1-alkyl-2-aryl-3-methylpyrroles 60 in high yields. The key step of this ring transformation is the ring opening of the pyrrolidine moiety followed by attack of the nitrogen atom at one of the carbonyl groups as shown in Figure 2.…”
Section: Degenerate Ring Transformations Of Five-membered Heterocymentioning
confidence: 99%